MENINGKATKAN KEMAMPUAN MEMBUAT KARYA SENI MOZAIK MENGUNAKAN MEDIA KONGKRIT PADA SISWA KELAS 4 SD NEGERI 4 KOTA BARAT - Nur Vadilla Katili; Wiwi Triyanty Pulukadang; Evi Hasim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formulation of the problem in this research is "can using mosaic learning media improve students' abilities in SBDP lessons in class IV at SDN 4 Kota Barat, Gorontalo City?" The aim of this research is to improve students' abilities through the application of Mosaic media in class IV SBDP lessons at SDN 4 West City. The type of research used is classroom action research. Data collection techniques include observation, tests and documentation. Based on research, data on student abilities was obtained in cycle I and cycle II. In cycle I, from a total of 19 students, only 11 students completed with a percentage of 57.89% and in cycle II, a total of 17 students completed with a percentage of 89.47%. The results of students' abilities in cycle II have reached the expected performance indicators. The conclusion in this research is that using mosaic media can improve students' ability to use media in SBDP lessons.